Efektivitas Pemberdayaan Aparatur Sipil Negara Dalam Peningkatan Pelayanan Publik Pada Badan Kepegawaian Daerah Kabupaten Tana Tidung - Jumia; Sabil, Ibnu; Malta (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2024)
Empowerment of regional apparatus in Tana Tidung Regency is one of the right policies to improve the performance of public services in all fields. The purpose of this study was to find out and analyze the effectiveness of ASN empowerment at the BKPSDM office of Tana Tidung Regency in improving public services, to find out and analyze what factors are obstacles in empowering ASN in improving the quality of public services, and to find out what solutions can be done by BKPSDM Tana Tidung Regency in the context of empowering regional apparatus to improve the quality of public services. The research method used is descriptive qualitative, with 14 respondents. The results of the study show that the effectiveness of ASN empowerment at the BKPSDM Office of Tana Tidung Regency in improving public services can be said to be quite good, when viewed from the work assignments given, work quality, work quantity, and cost effectiveness. While the timeliness in completing the work is not good enough. Some of the factors that become obstacles in ASN empowerment are: inadequate facilities, inadequate HR skills or skills in the office, the low level of discipline of Civil Servants at the Tana Tidung Regency BKPSDM office, and the employee performance evaluation program at the Tana Tidung Regency BKPSDM office has not been implemented properly. Responding to some of the existing weaknesses, the solution taken in the context of empowering regional apparatus to improve the quality of public services is to synchronize and harmonize the implementation of staffing regulations and optimize Bimtek and Training.